An Evaluation of the Impact of the Pension System on Income Inequality: USA, UK, Netherlands, Italy and Türkiye - Verberi, Can; Kaplan, Muhittin (Springer, 2024)
This study examines empirically the impact of various characteristics of pension systems, in particular their quality and integrity, on income inequality, utilizing micro-level data from the United States, United Kingdom, Netherlands, T & uuml;rkiye and Italy. To this end, the income inequality model, which includes public pension (or public/private pension mix), age, education, gender, marital status and employment as independent variables, has been estimated using quantile regression. The results provide a number of valuable information on the impact of the pension system on income inequality: (i) Public pension income significantly reduces overall income inequality across almost all inequality groups in all countries, except for the UK and the Netherlands; (ii) Different types of pension systems vary significantly in their redistributive effects on income; (iii) The empirical results also show that the effect of different pension systems on inequality changes by inequality groups significantly.
Keywords: Personal income inequality; Pension system types; Public/private pension mix; Quantile regression; D31; D63; E25; G23; H55